The Influence Of CEO's Face Masculinity, CEO Narcissism, Gender Diversity, And CEO Overconfidence On Tax Aggressiveness - Saputri, Indri Widya; Anisa Kusumawardani (SEAN Institute, 2024)
The COVID-19 pandemic has triggered significant economic disruptions worldwide, including in Indonesia, where the government implemented tax incentives to support businesses. While these measures are intended to ease economic pressures, they have also sparked concerns regarding tax aggressiveness, particularly among Shariah compliant companies, which are expected to uphold higher ethical standards. This study examines the impact of CEO characteristics specifically facial masculinity, narcissism, overconfidence, and gender diversity on tax aggressiveness in companies listed on the Indonesia Sharia Stock Index (ISSI). Utilizing a sample of 390 firms selected through purposive sampling, the research applies SPSS for data analysis. The findings indicate that tax aggressiveness is negatively and insignificantly influenced by CEO facial masculinity, positively and insignificantly influenced by CEO narcissism, negatively and significantly influenced by gender diversity, and positively and significantly influenced by CEO overconfidence.